Dickens and Prince a particular kind of genius - Hornby, Nick 1957- (Riverhead Book, 2022)
"From the bestselling author of Just Like You, High Fidelity, and Fever Pitch, a short, warm, and entertaining book about art, creativity, and the unlikely similarities between Victorian novelist Charles Dickens and modern American rock star Prince. Every so often, a pairing comes along that seems completely unlikely-until it's not. Peanut butter and jelly, Dennis Rodman and Kim Jong Un, ducks and puppies, and now: Dickens and Prince. Equipped with a fan's admiration and his trademark humor and wit, Nick Hornby invites us into his latest obsession: the cosmic link between two unlikely artists, geniuses in their own rights, spanning race, class, and centuries-each of whom electrified their different disciplines and whose legacy resounded far beyond their own time. When Prince's 1987 record Sign o' the Times was rereleased in 2020, the iconic album now came with dozens of songs that weren't on the original- Prince was endlessly prolific, recording 102 songs in 1986 alone. In awe, Hornby began to wonder, Who else ever produced this much? Who else ever worked that way? He soon found his answer in Victorian novelist and social critic Charles Dickens, who died more than a hundred years before Prince began making music. Examining the two artists' personal tragedies, social statuses, boundless productivity, and other parallels, both humorous and haunting, Hornby shows how these two unlikely men from different centuries "lit up the world." In the process, he creates a lively, stimulating rumination on the creativity, flamboyance, discipline, and soul it takes to produce great art."--
Keywords: Dickens, Charles -- 1812-1870; Prince -- Musiker -- 1958-2016; Dickens, Charles / 1812-1870; Prince; Dickens, Charles / 1812-1870 / Appreciation; Prince / Appreciation; Art appreciation; Biographies